DEVELOPING A MODEL OF TEACHING NARRATIVE TEXT: AN INTERCULTURAL APPROACH - Sumani, Sumani; Rosita Sari, Dwi; Arifin, Samsul (IKIP PGRI MADIUN, 2013)
The educational researches have been conducted for years; however, few of the research discussed the implementation of culture in the teaching English as a foreign language (TEFL). The research covers the issue especially in the extend of finding model of teaching narrative text implementing intercultural approach. The research implemented procedures of Reseach and Development (R & D) based on Borg & Gall. It was held from January 2013 to July 2013. The population of the research was the nine graders of Madiun Regency-wide, and the samples were 9B (Nine graders of B) SMP Negeri 1 Geger Madiun and 9C (Nine graders of C) SMP Negeri 2 Karangrejo Magetan. The data were analyzed qualitatively and quantitatively. The result showed that the model of teaching narrative text implementing intercultural consisted of six stages. The details were (1) Awareness Raising Phase involves Having short conversation with students toward the topic and material being learned; Having students listen and watch a monolog of narrative text (L1 narrative text); and Having students observe conversational and interactional features of the text individually, especially on the intercultural points; (2) Interactional Phase involves Leading conversation to the result of the text observed; Eliciting some possible cultural aspects of the text both verbally and un-verbally; Asking the students to do grouping of which each consists of three; Having students do group discussion to the cultural points of the text; (3) Reflective Phase involves Having discussion with students to the result of the conversational analysis; and Stating the intercultural points of the text explicitly; (4) Experimental Phase involves Having students read a narrative text (L2 narrative text) in group; Having students discuss the intercultural points of the text in group; and Having students do monolog of the text in group by concerning on the intercultural points; (5) Introspective Phase involves Having students evaluate the result of their monolog; and Having students compare the intercultural points of the text both L1 narrative text and L2 narrative text have been learned in group; and (6) Cultural Evaluation Phase involves Having students write a comparison and contrast of the intercultural points of the text both L1 narrative text and L2 narrative text have been learned individually.Keywords: Narrative Text, Intercultural, Reseach and Development